2023
DOI: 10.1039/d2cp05850b
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced high-temperature superconductivity in ternary Y–Zr–H compounds

Abstract: Compressed hydrogen-rich compounds have received extensive attention as appealing contenders for superconductors. Here, we found several stable hydrides YZrH6, YZrH8, YZr3H16, YZrH18 and a series of metastable clathrate hexahydrides in...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 49 publications
2
1
0
Order By: Relevance
“…Recently, Zhang and coworkers 17 carried out cluster expansion calculations coupled with CSP to determine the lowest enthalpy geometries resulting from the reaction of SrB 3 C 3 and RbB 3 C 3 to form Rb x Sr 1−x B 3 C 3 with different metal ratios (x = 0.125−0.5) and considering different colorings (metal atom distributions 53 ). Relevant for our study, they found that a Pm3̅ RbSrB 6 C 6 compound, wherein the shortest metal−metal contacts were between Rb and Sr, possessed the most negative enthalpies of formation (though for the CaYH 12 analogues, different colorings were preferred 54,55 ). Similarly, the most stable coloring for the Rb 0.4 Sr 0.6 B 3 C 3 stoichiometry corresponded to a homogeneous distribution of the two metal atoms.…”
Section: ■ Results and Discussionsupporting
confidence: 52%
“…Recently, Zhang and coworkers 17 carried out cluster expansion calculations coupled with CSP to determine the lowest enthalpy geometries resulting from the reaction of SrB 3 C 3 and RbB 3 C 3 to form Rb x Sr 1−x B 3 C 3 with different metal ratios (x = 0.125−0.5) and considering different colorings (metal atom distributions 53 ). Relevant for our study, they found that a Pm3̅ RbSrB 6 C 6 compound, wherein the shortest metal−metal contacts were between Rb and Sr, possessed the most negative enthalpies of formation (though for the CaYH 12 analogues, different colorings were preferred 54,55 ). Similarly, the most stable coloring for the Rb 0.4 Sr 0.6 B 3 C 3 stoichiometry corresponded to a homogeneous distribution of the two metal atoms.…”
Section: ■ Results and Discussionsupporting
confidence: 52%
“…Based on these reasons, the T c value of P4/mmm-YHfH 8 has been effectively enhanced to 47 K. Notably, in YHfH 18 phases at 400 GPa, metal atoms motions in the lowest part of the phonon bands (< 10 THz) only occupy 18% of the total λ, while all other vibrational modes up to 82% (> 25 THz) are dominated by H atoms. Obviously, YHfH 18 possess the highest predicted T c value 130 K among the four stable structures, which is close to other Hrich materials such as YZrH 18 (156 K) 33 and LiP 2 H 14 (169 K) 56 , but higher than MgH 12 (60 K) 57 , YCH 12 (112 K) 58 , YSH 6 (91 K) 59 , Ca 2 B 2 H 13 (89 K) 60 and Mg(ScH 4 ) 3 (10 K) 61 . This result highlights that the highfrequency H atom vibration exhibits a signi cant contribution to the electron-phonon coupling in YHfH 18 structure, which is coincide with the analysis result of large H-DOS proportion at the Fermi level.…”
Section: Dynamical Properties and Electron-phonon Couplingsupporting
confidence: 66%
“…In accordance with these principles and employing a first-principles calculation in the Ca-Zr-H and Ca-Hf-H ternary systems [131], CaHfH 12 exhibited a T c of approximately 360 K at 300 GPa, and CaZrH 12 displayed a T c of approximately 290 K at 200 GPa. Zhao et al studied the pressure-induced high-temperature superconductivity in ternary Y-Zr-H compounds [132]. Through first-principles calculation, they identified stable hydrides such as YZrH 6 , YZrH 8 , YZr 3 H 16 , and YZrH 18 , as well as metastable clathrate hexahydrides.…”
Section: Selecting Suitable Precompression Elements To Obtain Ternary...mentioning
confidence: 99%